2014
DOI: 10.3109/09553002.2014.899446
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic properties of radionuclide-conjugated Cetuximab without and in combination with external irradiation in head and neck cancer cells in vitro

Abstract: Our findings show that Cetuximab-conjugated (90)Y has a significant potential to eradicate human SCC cells. A combination of radioimmunotherapeutic compounds and external radiotherapy might be a promising treatment strategy for clinical application.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…Based on this success different approaches for development of anti-EGFR based theragnostics was studied using different antibodies, chelators and radionuclide combinations for radioimmunotherapy of EGFR expressing tumor entities [ 19 26 ]. Further, preclinical rationales for combined anti-EGFR EndoRT with EBRT were developed [ 13 , 27 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…Based on this success different approaches for development of anti-EGFR based theragnostics was studied using different antibodies, chelators and radionuclide combinations for radioimmunotherapy of EGFR expressing tumor entities [ 19 26 ]. Further, preclinical rationales for combined anti-EGFR EndoRT with EBRT were developed [ 13 , 27 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, Sefl et al showed that neglecting the initial uptake phase will lead to a substantial overestimation of the absorbed dose, and thus, an underestimation of cell survival [ 78 ]. Nonetheless, 15 out of the 27 studies reporting survival vs. dose (52%) evaluated the RP uptake at only a single time-point and neglected biological decay, which can result in an overestimation of the absorbed dose [ 10 , 14 , 35 , 37 , 38 , 39 , 41 , 66 , 79 , 80 , 81 , 82 , 83 , 84 , 85 ].…”
Section: Preclinical Dosimetrymentioning
confidence: 99%
“…However, SAS and FaDu were already controlled after RIT treatment alone in spheroids as well as 2D cultures. 58,59 The obviously higher RIT efficacy in vitro than in xenografts may be explained by differing RIT doses used in the studies. Regardless of the limitations of efficacy tests, in vitro cell culture models offer important possibilities to study other end points such as cellular binding and uptake 55,57,59 as well as downstream signalling.…”
Section: 65mentioning
confidence: 99%
“…Regardless of the limitations of efficacy tests, in vitro cell culture models offer important possibilities to study other end points such as cellular binding and uptake 55,57,59 as well as downstream signalling. 32,57,58 Accordingly, in vitro models should be used to uncover underlying mechanisms and can give indications on efficacy. However, to evaluate the therapeutic benefit of combined treatment strategies, in vivo studies are inevitable for translation into the clinic.…”
Section: 65mentioning
confidence: 99%